EXPLORING THE FACTORS AFFECTING THE UNIVERSITY STUDENTS' WILLINGNESS TO READ ENGLISH TEXTBOOKS (Al-Aasar, 2025)
English textbooks remain a core resource in higher education, yet many university students demonstrate limited willingness to engage with them. Understanding the factors that shape this willingness is vital for improving reading motivation and learning outcomes. This study explores the factors affecting university students’ willingness to read English textbooks, with a focus on both student and teacher perspectives. A qualitative approach was employed, using semi-structured interviews with seven undergraduate students and three university teachers from different academic disciplines. The interviews were transcribed and analyzed thematically to identify recurring patterns and insights. The findings reveal that students’ willingness to read English textbooks is influenced by multiple interrelated factors. Personal factors such as language proficiency, confidence in reading, and prior exposure to English texts emerged as important determinants. Pedagogical practices, including the clarity of teacher guidance, use of pre-reading strategies, and alignment of textbook content with assessments, were also found to strongly affect students’ engagement. Contextual influences such as time constraints, workload, peer support, and the increasing availability of digital and AI-based alternatives further shaped students’ reading behavior. Teachers emphasized the need for scaffolding strategies, interactive discussions, and institutional support to encourage deeper engagement with textbooks. The study highlights that fostering students’ willingness to read requires a comprehensive approach that combines motivational teaching strategies, supportive learning environments, and the integration of relevant technologies. These insights provide practical implications for educators and curriculum planners aiming to strengthen academic literacy in multilingual university contexts.